2022
DOI: 10.1186/s12885-021-09150-3
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of BMP-2 by tumor-associated macrophages (TAM) promotes microcalcifications in breast cancer

Abstract: Introduction Breast microcalcifications is a characteristic feature in diagnostic imaging and a prognostic factor of breast cancer. However, the underlying mechanisms of breast microcalcifications formation are not fully understood. Previous studies have shown that upregulation of bone morphogenetic protein 2 (BMP-2) is associated with the occurrence of microcalcifications and tumor-associated macrophages (TAMs) in the tumor microenvironment can secrete BMP-2. The aim of this study is to elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 60 publications
(70 reference statements)
0
18
0
1
Order By: Relevance
“…Previous studies indicated that compared to in vivo differentiated peritoneal macrophages, BMDMs lie further toward the M1 end of the M1–M2 polarization spectrum [ 44 ]. Interestingly, BMP-2 itself was shown to be produced by M2 macrophages [ 45 , 46 ]. Thus, we searched for M2 marker genes among those upregulated by the last 48 h DHR treatment during macrophage differentiation to determine whether retinoid-treatment might promote M2 polarization.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that compared to in vivo differentiated peritoneal macrophages, BMDMs lie further toward the M1 end of the M1–M2 polarization spectrum [ 44 ]. Interestingly, BMP-2 itself was shown to be produced by M2 macrophages [ 45 , 46 ]. Thus, we searched for M2 marker genes among those upregulated by the last 48 h DHR treatment during macrophage differentiation to determine whether retinoid-treatment might promote M2 polarization.…”
Section: Resultsmentioning
confidence: 99%
“…For many years, breast calci cations have always been used as an indicator for the diagnosis of early breast cancer, but its underlying mechanism has not yet been fully understood. Previous studies has demonstrated that secretion of BMP-2 by TAMs could promote the deposition of microcalci cations [11,12]. As a conserved branch of the TGFβ superfamily, BMP-2 has been shown to be associated with the upregulating the expression of RUNX2, which plays an important role in osteoblasts and bone formation, and chondrocyte maturation [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Alizarin red S staining of breast cancer cells was performed [12]. Alizarin red S staining of mice's tumor was done as follows: after depara nization, alizarin red S (G1038, Servicebio, Wuhan China) was added to the sections for 5 min and the sections were washed.…”
Section: Alizarin Red S Staining and Quanti Cation Of Calci Cationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They play an important role in the growth and development of the body by coordinating the differentiation, proliferation, and apoptosis of cells in different tissues and organs ( 77 ). Many studies have revealed that BMPs not only regulate bone and cartilage but also exert a variety of biological processes in the development of cancers ( 78 ), including breast cancer ( 79 ), ovarian cancer ( 80 ), and lung cancer bone metastasis ( 81 ). The expression level of BMP2 is related to the degree of tumor malignancy and GBM patient survival; therefore, it is being considered as a prognostic marker for glioma ( 82 , 83 ).…”
Section: Discussionmentioning
confidence: 99%